Optimization, Fabrication and Characterization of Novel Meloxicam-Loaded Surface Attached Solid Dispersions to Ameliorate its Aqueous Solubility and Dissolution Employing Spray-Drying Technique - Shumaila Shafique, Ubed-Ur-Rehman Mughal, Abdullah Dayo, Omer Mustapha, Hina Saleem, Sabahat Naeem, Salman Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To formulate unmodified crystalline meloxicam solid dispersions by the use of surfactants and polymer. This polymeric particulate system is named as meloxicam-loaded surface attached solid dispersion (MSDs). Methodology: This experimental study was conducted at Lab of Physical and Industrial Pharmacy, Hanyang University, South Korea. The duration of this study was around seven months. The first phase of this study (optimization and fabrication) was completed within 3 months, while, solubility, dissolution and physicochemical characterization was completed in next 4 months. These surfaces attached solid dispersions were prepared by using spray drying technology. Moreover, HPMC and SLS were used as hydrophilic carriers. Various MSDs were prepared using carriers/drug, and were evaluated for aqueous solubility and dissolution studies. Results: Amongst different formulation prepared, MSDs3 having Meloxicam/HPMC/SLS in a (1:0.5:0.5) gave the highest solubility and dissolution (i.e. from 0.25 ±0.17ug/ml of meloxicam to 153 ±5.3ug/ml). Moreover, dissolution was enhanced from 2.96 ±0.55% to 47 ±1.07% at 15 minutes. Furthermore, physicochemical characterization was performed by scanning electron microscopy (SEM), differential scanning calorimetry (DSC) and powder X-ray diffraction (PXRD). Conclusion: In conclusion we can predict a better solubility and dissolution of meloxicam in surface attached solid dispersion. Keywords: Meloxicam, solubility enhancement, spray drying, surface attached, solid dispersion